EDP Renewables equity valuation thesis - Salgueiro, David Manuel Salgueiro Amaral (2017)
This dissertation valuates EDP Renewables, a subsidiary company from EDP, listed on PSI20, operating in the Utilities industry - renewables energies field. Due to the energy sector transformations, the continuous search for clean sources of power plus the plausible worldwide utilities industry transformation, becomes imperative to valuate companies that can be game changers. To achieve the value per share it was used the Discounted Cash Flow, both the Free Cash Flow to the Firm & the Free Cash Flow to Equity approaches, giving us an equity value of m7.569€ and m7.564€ respectively – this translates in an 8.68€ and 8.67€ price per share. Based on the Dividend Discount Model, the equity value is m7.555€ meaning a price per share of 8.66€. According with the Multiples EV/Revenue, EV/EBITDA and Price/CF per share, we reached prices of 8.19€, 8.88€ and 8.57€. A real option approach was also developed to quantify a recent investment project (wind farm) in the UK. Due to the uncertainty related with the industry and the markets, sensitivity analysis were incorporated into the model to absorb real life volatility. In the end, we reached a final price of 8.6€ per share and we recommend a buy action (actual price: 7.11€). As benchmark for the final price per share were used valuations from Morgan Staley (8.3€) and Haitong Bank (8.2€) which allowed us to conclude that the value reached in this thesis is in line with the opinion of others financial institutions and provides this dissertation with practical usefulness.